IMPROVE CRITICAL THINKING ABILITY AND MATHEMATICAL COMMUNICATION OF INFORMATION SYSTEMS STUDENTS WITH THE MISSOURI MATHEMATICS PROJECT (MMP) LEARNING - Nurapriani, Fitria; Sulistya Kusumaningrum, Dwi; Suryana (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to improve the ability of critical thinking and mathematical communication of Information Systems students by learning the Missouri Mathematics Project (MMP). MMP is a program designed to assist lecturers in the effective use of exercises in the form of project worksheets so that students achieve improved learning outcomes. MMP emphasizes cooperative learning and student independence. The method used is a quasi-experimental method with a research design using pretest and posttest without randomization (Group Pretest Posttest Design). The study population was Information Systems students at the Faculty of Engineering and Computer Science, Buana Perjuangan University, Karawang. Samples were taken as many as 2 classes, one class as an experimental class (MMP learning) and another class as a control class (conventional learning). The average scores of the two classes did not differ significantly, namely the critical thinking ability of MMP class students before learning 6.41 (32.05% of ideal scores) and conventional classes 5.84 (29.20% of ideal scores). The average score of the mathematical communication skills of the two classes did not differ significantly, namely the MMP class of 6.35 (31.75% of the ideal score) and the conventional class of 7.29 (36.45% of the ideal score). Pretest critical thinking and communication skills of the two classes are still not good when compared with the ideal score.